Peran Manajemen Sumber Daya Manusia Dalam Peningkatan Mutu Pendidikan Madrasah - Devi Sartika; Jumira Warlizasusi; Ifnaldi; Elce Purwandari; Zuhri (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This study aims to investigate the role of human resource management in improving the quality of education at Madrasah Aliyah Ulul Albab Lubuklinggau City. Human resource management (HRM) has a crucial role in improving the quality of education. Madrasah Aliyah Ulul Albab is an Islamic educational institution in Lubuklinggau City which is committed to providing quality education to its students. This study uses the literature study method which involves an analysis of related articles, books and documents. Several factors analyzed in this study include the recruitment and selection of teaching staff, teacher professionalism development, performance management, and internal communication. The results of the study indicate that the role of human resource management plays an important role in improving the quality of education at Madrasa Aliyah Ulul Albab. First, the rigorous and competent recruitment and selection of teaching staff will ensure that only the best teachers are accepted at this madrasa. Second, the development of teacher professionalism through training, workshops and self-development activities will improve the quality of teaching. Third, good performance management will ensure constructive evaluation and feedback to teachers to improve the quality of their teaching. Lastly, effective internal communication between madrasah leaders, teachers and staff will facilitate good cooperation in achieving set educational goals